International portfolios, capital accumulation and foreign assets dynamics - Nicolas Coeurdacier; Robert Miguel W. K. Kollmann; Philippe J. Martin (Deutsche Bundesbank, 2008)
Despite the liberalisation of capital flows among OECD countries, equity home bias remains sizable. We depart from the two familiar explanation of equity home bias: transaction costs that impede international diversification, and terms of trade responses to supply shocks that provide risk sharing, so that there is little incentive to hold diversified portfolios. We show that the interaction of the following ingredients generates a realistic equity home bias: capital accumulation, shocks to the efficiency of physical investment, as well as international trade in stocks and bonds. In our model, domestic stocks are used to hedge fluctuation in local wage income. Terms of trade risk is hedged using bonds denominated in local goods and in foreign goods. In contrast to related models, the low level of international diversification does not depend on strongly countercyclical terms of trade. The model also reproduces the cyclical dynamics of foreign asset positions and of international capital flows.
Keywords: G1; F3; F2; 330; capital accumulation; international equity and bond portfolios; capital flows; current account; valuation effects; terms of trade; Internationale Kapitalmobilität; Portfolio-Investition; Home Bias Puzzle; Terms of Trade; Kapitalproduktivität; Zahlungsbilanzungleichgewicht; Theorie